"Road to 10 Years Brotherground" Concert by Grounderz in Surabaya: A Review of Management Practices - Leli Mayalingga (Repertoar, 2026)
This study aims to analyze the management of the “Road to 10 Years Brotherground” concert by Grounderz in Surabaya, as well as audience responses. The method used was descriptive qualitative research through observation, interviews with the organizers and 50 audience members, and documentation. The results show that the organizing committee implemented management functions, including planning, organizing, directing, and controlling. Planning encompassed determining the concept, lineup, budget, ticket prices, and promotional strategies, while a clear division of tasks supported coordination during the event. Control was exercised to ensure proper execution and to serve as a basis for evaluation. Although the target audience was not reached due to location-related factors, the concert still received a positive response. Based on the Stimulus-Organism-Response (SOR) theory, the majority of attendees were satisfied and expressed interest in attending the next concert. These findings indicate that Brotherground’s strength lies in the consistency of its concept and its close connection to the extreme music community.